Comparative analysis of three serum‐free light‐chain detection systems in the diagnosis of multiple myeloma. (20th January 2022) - Zhu, Guoqing; Fu, Xue; Ren, Yansong; Wang, Yansheng; Wang, Shoulei; An, Gang
Abstract: Objective: To observe the comparability of serum‐free light chain (sFLC) detected by Beckman, Siemens, and Binding Site. Methods: In this study, 110 patients who were diagnosed with multiple myeloma in State Key Laboratory of Experimental Hematology from November 2019 to August 2020. According to the instructions of equipment and reagent manufacturers, three detection systems (Binding Site, Beckman, and Siemens) were used to detect the serum‐free light chain of selected analysis samples. Meanwhile, sFLC test results of the three instruments were compared. According to EP9‐A3 guide, correlation and consistency were conducted by Bland‐Altman and Passing‐Bablok regression. Results: The free kappa light‐chain serum samples and the free lambda light‐chain samples were quantitatively analyzed by the three systems. Binding Site, Beckman, and Siemens free light‐chain detection results were as follows: FLC‐κ: 42.23 (3.73, 423), 34.55 (6.5, 194), 39.85 (3.73, 423); FLC‐λ: 31.46 (1.39, 8180.42), 32 (4.3, 275), 37.65 (2.28, 526); rFLC (FLC‐κ/FLC‐λ): 1.21 (0, 131.28), 0.96 (0.02, 43.49), 1.04 (0.04, 40.29). The Kappa valuation of FLC‐κ between Beckman and Binding Site is 0.97, Kappa valuation of FLC‐λ between Beckman and Binding Site is 0.96, Kappa valuation of rFLC between Beckman and Binding Site is 0.97. The Kappa valuation of FLC‐κ between Siemens and Binding Site is 0.96, Kappa valuation of FLC‐λ between Siemens and Binding Site is 0.88, Kappa valuation of rFLC between Siemens and Binding Site is 0.94. Conclusion: All of the three systems can meet the needs of diagnosis and treatment in clinical application. These analyses showed a very good concordance between Beckman, Siemens, and Binding Site.